2010
DOI: 10.1007/s11904-010-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing

Abstract: The availability of rapid, point-of-care (POC) tests has significantly expanded the capacity of both developed and resource-constrained countries (RCCs) to diagnose HIV, with immunochromatographic tests most commonly used in these settings. This has been especially important in programs for prevention of mother-to-child transmission, in both RCCs and the developed world. However, suitable POC tests are not yet commercially available for diagnosis of neonatal HIV, where persistence of maternal antibody in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…As with other rapid testing [19], both rapid tests using oral and fingerstick methods require significant adaptation of test instructions as well as clear labeling and numbering of all components to correspond with test instructions; instructions that specify more clearly how to handle the sample collection device and properly collect a sample may be helpful. In particular, instructions need to be developed and tested for understanding, including populations with low literacy levels [20,21]. Use of pictures is essential and, in some settings, additional local languages may be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…As with other rapid testing [19], both rapid tests using oral and fingerstick methods require significant adaptation of test instructions as well as clear labeling and numbering of all components to correspond with test instructions; instructions that specify more clearly how to handle the sample collection device and properly collect a sample may be helpful. In particular, instructions need to be developed and tested for understanding, including populations with low literacy levels [20,21]. Use of pictures is essential and, in some settings, additional local languages may be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Another study encourages initiation with point-of-care testing as the best solution to avoid issues of sample transport and hence fast delivery of results. [14] Recommendations indicate that if an appointment is scheduled with a woman to receive test results (step 4), it either needs to be kept or the woman needs to be contacted to reschedule the appointment. One study found that HIV-infected mothers enrolled in HIV care were less likely to fail to return for their infant's HIV test result (aRR 0.51; 95% CI (0.3 -0.9), [5] therefore providing ART to all pregnant women may lead to a better return.…”
Section: Discussionmentioning
confidence: 99%
“…However, by eliminating the need to transport samples or to return to a clinic to retrieve the test results, a rapid point-of-care test for infant HIV diagnosis 14 could still greatly enhance the operational feasibility of early infant diagnosis programmes in resource-poor settings.…”
Section: Box 1 Summary Of Main Lessons Learntmentioning
confidence: 99%